Influence of trace aromatics on the chemical growth mechanisms of Titan aerosol analogues. (June 2017) - Gautier, Thomas; Sebree, Joshua A.; Li, Xiang; Pinnick, Veronica T.; Grubisic, Andrej; Loeffler, Mark J.; Getty, Stephanie A.; Trainer, Melissa G.; Brinckerhoff, William B.
Abstract: The chemical structure and formation pathways of Titan aerosols remain largely unknown. In this work, we studied the effect of trace aromatics on the chemical composition and formation pathways of laboratory analogues of Titan's organic aerosols. The aerosol analogues were produced using four different trace aromatic molecules, comprised of one or two aromatic rings, each with or without a nitrogen heteroatom. Samples were then analyzed by laser desorption/ionization Mass Spectrometry (LDMS), revealing a high variability in the sample composition depending on the trace aromatic used. Our work reveals that the final chemical structure of the aerosols depends strongly on the number of aromatic rings in the trace molecule, leading either to a polymeric or to a random co-polymeric growth of the sample. These different chemical structures can affect the physical properties of the aerosol. Future analysis of Titan's aerosols using better resolution could potentially determine whether either of the growth hypotheses are preferred. Highlights: The influence of trace aromatic on Titan aerosol growth is investigated. Growth of the aerosol can either be polymeric or random co-polymeric. Growth process is mostly affected by the number of ring in trace aromatic. Current observational data of Titan cannot discriminate both growth mechanism.